Workshop Review: TRACamp, A Roman Experimental Archaeology Workshop - Lee Graña (EXARC, 2019)
Experiments have always been an integral part of scientific investigation. Nevertheless, the more complex nature of heritage studies such as archaeology and ancient history -often interdisciplinary by nature- has delayed the development of clear and reliable methodologies for including experiments into broader research objectives. Apprehension towards inclusion of experiments seems to increase when periods have richer sources of literary and archaeological evidence, and they are indeed far more numerous in prehistoric studies.